Accidental Intramuscular Isoprenaline in Early Pregnancy: The Effects, Management and Outcome - Mostafi, Mamun; Rahman, Md Anisur; Mollick, Md Torab; Haq, Md Naimul; Rafi, Ahmed (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Isoprenaline is a beta-adrenergic agonist, used for the treatment of cardiovascular emergencies like hypotensive shock or sever bradycardia. This drug is not indicated to use in bolus form either intramuscularly or intravenously. Accidentally a 22 year old pregnant woman was given an intramuscular injection of two mg Isoprenaline. It was a lethal dose, fortunately the patient survived. This article narrated the events, the ECG changes, management and outcome of the patient and pregnancy. J Bangladesh Coll Phys Surg 2016; 34(2): 108-111